The accounting world post-Enron, Tyco, Vivendi, WorldCom, Xerox...: reflections on being part of the solution / Shahrokh M. Saudagaran - Saudagaran, Shahrokh M. (Faculty of Accountancy & Accounting Research Institute (ARI), 2003)
The events of the past year have cast a spotlight on accounting and accountants. While most of the media coverage has related to the problems in the United States, the rest of the world, including Asia, is not exempt from these concerns. The severe losses suffered by investors have resulted in a dramatic decline in confidence in the stock markets. This can have negative long-term effects if the erosion in confidence causes investors to continue to stay away from the markets. There is much that can be done to improve the integrity of financial reporting through greater accountability, the restoration of resources devoted to the audit function, and better corporate governance policies. The current paper discusses the roles of educators and academic accounting association towards improving accounting education and practice in Asia.